Corrosion behavior of ZrO2-TiO2 composite coatings produced on titanium alloy via plasma electrolytic oxidation - Li, Hui; Ma, Guofeng; Wang, Ziyao (Surface & coatings technology, 2023)
TiO2-ZrO2 composite coating was fabricated on TC4 titanium alloy via plasma electrolytic oxidation (PEO) in an alkaline electrolyte composed of Na2SiO3 and KOH. The effect of the content of K2ZrF6 as an electrolyte additive on the microstructure, elemental composition, phase structure, thickness, hardness, adhesion and corrosion resistance of PEO coating was investigated. The results show that the addition of K2ZrF6 contributed to the enhancement of coating thickness (from 4.04 ± 0.62 μm to 11.44 ± 0.35 μm) and hardness (488.4 HV to 779.8 HV). As the K2ZrF6 concentration increased, both the quantity and diameter of micropores on the surface of the PEO coatings decreased firstly and then increased. The minimum porosity and pore size were obtained in the electrolyte containing 6 g/L K2ZrF6. The coatings were mainly composed of Ti, anatase TiO2 and rutile TiO2. EDS test proved that K2ZrF6 successfully participated in the PEO reaction. The composite coating prepared in silicate electrolyte system with 6 g/L K2ZrF6 exhibited the highest corrosion resistance. Furthermore, the formation mechanism of the ZrO2-TiO2 composite coating was discussed in detail. •ZrO2-TiO2 coatings were prepared on TC4 by PEO reaction.•ZrO2-TiO2 coatings have compact and uniform morphology.•ZrO2-TiO2 coatings have high hardness and superior corrosion resistance.•The formation mechanism of the ZrO2-TiO2 composite coatings were discussed.